Daily biofilm control and oral health: Consensus on the epidemiological challenge-Latin American Advisory Panel - Rode, Sigmar de Mello [UNESP]; Gimenez, Xiomara; Montoya, Victoria Criado; Gómez, Mariel; de Blanc, Silvia Lopez; Medina, Marco; Salinas, Elmer; Pedroza, Janeth; Zaldivar-Chiapa, Rosi Maria; Pannuti, Claudio Mendes; Cortelli, José Roberto; Oppermann, Rui Vicente (FapUNIFESP (SciELO), 2012)
Our understanding of dental plaque biofilm has evolved since the nonspecific plaque hypothesis that considered plaque as a nonspecific mass of native microorganisms that, because of lack of oral hygiene, builds up in proportions great enough to overcome the host resistance threshold and affect the tooth structure and tooth supporting tissues. A great diversity of microorganisms-over 700 species-was detected in the oral cavity, and evidence shows that the investigation of specific microorganisms or associations of microorganisms as etiological agents for periodontal diseases and caries is not a simplistic approach. Although clinical evidence shows that oral mechanical hygiene is fundamental to prevent and control caries and periodontal disease, it is important to highlight that optimal control is not achieved by most individuals. Thus the complementary use of chemotherapeutic agents has been investigated as a way to overcome the deficiencies of mechanical oral hygiene habits, insofar as they reduce both plaque formation and gingival inflammation, and represent a valid strategy to change the biofilm and maintain dental and periodontal health. The role of the dental professional is to monitor patients and offer them the best recommendations to preserve oral health throughout their life. With this in mind, chemical control should be indicated as part of daily oral hygiene, together with mechanical procedures, for all individuals who present supragingival and/or subgingival biofilm, taking into account age, physical and/or psychological limitations, allergies, and other factors.
Keywords: Cetylpyridinium; Dental plaque; Gingivitis; Mouthwashes; Oils; mouthwash; biofilm; gingivitis; health; human; methodology; microbiology; mouth hygiene; South and Central America; standard; tooth plaque; Biofilms; Dental Plaque; Humans; Latin America; Oral Health; Oral Hygiene